Noonan Syndrome with Hepatomegaly and Persistently Elevated Liver Enzymes: A Case Report - Islam, Md Aminul; Begum, Shamrose; Haque, Md Azizul (TAJ: Journal of Teachers Association, 2022)
Noonan’s syndrome is a polymorphic disorder with some facial features, congenital heart defects, cryptorchidism, etc., and also associated with some autoimmune diseases, lymphatic dysplasias. Here we are reporting a nine years old boy with Noonan's syndrome who has hepatomegaly with persistently raised hepatic enzymes, which remained unexplained. TAJ 2022; 35: No-1: 137-140